Primary Renal Synovial Sarcoma: An Oncologic Surprise() - Moorthy, H. Krishna (Urol Case Rep, 2014)
Primary renal synovial sarcoma is a rare tumor having a specific chromosomal translocation t(X; 18) (p11.2; q11.2). The clinical features of this tumor and radiologic appearances are quite similar to those of renal cell carcinoma. Confirmatory diagnosis requires fluorescent in situ hybridization or reverse transcriptase polymerase chain reaction validation for differentiating the tumors from sarcomatoid renal cell carcinoma. We present a case of primary renal synovial sarcoma that was diagnosed in a middle-aged man.